Elevating the Inner-Consciousness “Third-Eye” Through “Vedic Manas Yoga” Practice (International Journal of Ayurveda and Pharma Research, 2024)
‘Third-Eye Chakra’, also known as ‘Ajna Chakra’ in Sanskrit, is the sixth of the body's seven major Chakras. It is also known as the "perception center" and, said to be the seat of soul and the portal to higher awareness. It is essential for achieving greater awareness and serves as the focus of concentration during Asana or meditation practices. Ajna Chakra corresponds to the hypothalamus, pituitary gland, and pineal gland, as well as the eyes, ears, and nose in the physical body. Vedic manas yoga is a holistic approach to yoga that integrates concepts from the Vedas, ancient Indian literature, with practices that attempt to balance the mind, body, and spirit. This study was conducted to develop the inner consciousness and awake the dormant powers of individual participants using Vedic manas yoga. In this observational study, a total 30 physically and mentally healthy subject aged in between 5 to 15 years of both gender from Patanjali Gurukulam, Haridwar, were included. The Pre- and Post-treatment SF-36 scores were statistically evaluated using paired t-test. There was a significant difference (p